Producing Video Project-Based Learning Using Online Game to Increase Students’ Engagement and Speaking Competence of Students Grade 9, State Junior High School 1 Slawi in The COVID-19 Pandemic Period - Bunyamin, Bunyamin (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
Producing Video Project-Based Learning Using Online Game To increase students’ engagement and speaking competence of students grade 9, State Junior High School 1 Slawi in the covid-19 pandemic period. The problem of this best practice is how could the implementation of producing video project-based learning using online game increase students’ engagement and speaking competence of grade 9, State Junior High School 1 Slawi in the covid-19 pandemic period? The aim of this best practice is to describe that the implementation of producing video project-based learning using online game could increase students’ engagement and speaking competence of grade 9, State Junior High School 1 Slawi in the covid-19 pandemic period. This best practice was conducted in grade 9 of State Junior Highs School 1 Slawi, the first semester of the academic year 2021-2022. Before implementing the producing video project-based learning using online game , students’ engagement achieved 40%, the average of speaking competence score achieved 72,9 and the students who achieved the passing grade only 30% among 99 students. After implementing the producing video project-based learning using online game, the students’ engagement increased to 95%, the average of students’ competence score increased to 82, those who achieved the passing grade increased to 83 students (80%), and those who haven’t achieved the passing grade only 16 students (19,79%). Based on that result, it could be concluded that producing video project-based learning using online game could increase students’ engagement and speaking competence of grade 9, State junior High School 1 Slawi in the covid-19 pandemic period which was in the first semester of the academic year 2021-2022.